Penggunaan Bahasa Daerah dalam Program Televisi JTV sebagai Upaya Pemberdayaan Kearifan Lokal - Ika Ayu Nurlela; Khadijah Khadijah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines the use of regional languages, especially Suroboyoan language, in local television programs JTV as an effort to empower local wisdom. The Pojok Kampung program that uses Suroboyoan language as the language of news delivery is the main focus. The case study method is used with data collection through interviews, broadcast observations, and supporting documents. The results show that the use of regional languages ​​is effective in preserving local culture, strengthening community identity, and becoming a medium for expressing local wisdom. This program received a positive response from the community even though it caused controversy. In conclusion, JTV plays an important role in empowering local wisdom through regional languages ​​in its broadcasts.